Development of pea protein and high methoxyl pectin colloidal particles stabilized high internal phase pickering emulsions for β-carotene protection and delivery. (April 2021) - Yi, Jiang; Gan, Chao; Wen, Zhen; Fan, Yuting; Wu, Xuli
Abstract: The demand for novel-delivery systems with natural biopolymers to stabilize and deliver biologically active and functional β-carotene (BC) is increasing. Protein-polysaccharide colloidal particles exhibited great potential for the stabilization and delivery of BC-loaded high internal phase Pickering emulsions (HIPPEs). In this study, pea protein isolate (PPI) and high methoxyl pectin (HMP) colloidal particles were fabricated and used for stabilizing and delivering BC-loaded HIPPEs. PPI-HMP complexes exhibited spherical shapes with Z-average diameters of 379 nm at pH 4.0. Turbidity, zeta-potential, and fluorescence spectroscopy results evidenced that the formations of PPI-HMP colloidal particles were primarily driven by electrostatic attraction. pH, and storage stability of HIPPEs was profoundly enhanced with PPI-HMP colloidal particles. HIPPEs with PPI-HMP colloidal particles exhibited the highest BC retention and the chemical stability of BC at pH 6.0 (68.3%) was pronouncedly higher than that at pH 3.0 (49.5%). Confocal laser scanning microscope (CLSM) graphs demonstrated HIPPEs were stabilized by a dense network surrounding the oil droplets. Compared to corn oil (control), both PPI and PPI-HMP complex-stabilized HIPPEs exhibited a higher extent of lipolysis and BC bioaccessibility. Both lipolysis extent and BC bioaccessibility of HIPPEs with PPI-HMP colloidal particles (36.5%, and 25.8%) were lower than those with PPI (42.7%, and 31.4%). This research evidenced that PPI-HMP complex colloidal particles can be synthesized for fabricating stable BC-loaded HIPPEs with enhanced chemical stability and controlled release property. Graphical abstract: Image 1 Highlights: PPI-HMP complex colloidal particles were fabricated as HIPPEs stabilizers. A one-step method is developed for fabrication of stable HIPPEs. PPI-HMP particles enhanced the stability of HIPEs against pH variation. PPI-HMP particles enhanced the chemical stability of encapsulated β-carotene. HIPPEs were able to increase the in vitro bioaccessibility of β-carotene.